Cloning of human and bovine homologs of SNF2/SWI2: a global activator of transcription in yeast S. cerevisiae. - Okabe, I (1992)
We performed positional cloning of genes carried on yeast artificial chromosomes that span a human translocation breakpoint associated with a human disease and isolated by chance human and bovine genes with strong homology to the S. cerevisiae genes, SNF2/SWI2 and STH1, and the D. melanogaster gene brahma. We report here sequence analysis, expression data, and functional studies for this human SNF2-like gene (hSNF2L) and its bovine homolog (bovSNF2L). Despite strong homology at the amino acid level, hSNF2L is not capable of complementing the yeast mutations snf2 or sth1 in S. cerevisiae. Furthermore, in contrast to SNF2 itself, a fusion protein consisting of the DNA binding domain of LexA and hSNF2L did not transactivate a reporter gene downstream of LexA binding sites in a yeast expression system. The strong similarity between hSNF2L and these yeast and drosophila genes suggest that the mammalian genes are part of an evolutionarily conserved family that has been implicated as global activators of transcription in yeast and fruitflies but whose function in mammals remains unknown.